2016
DOI: 10.1016/j.ijmyco.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Does intensified case finding increase tuberculosis case notification among children in resource-poor settings? A report from Nigeria

Abstract: Intensified case finding combined with capacity building, provision of work aids/guidelines, and TB health education can improve childhood-TB notification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 9 publications
3
37
0
Order By: Relevance
“…Studies from Pakistan, India, Nepal and Nigeria have shown that intensified case finding can result in large increases in childhood TB case notification [9,[13][14][15]. Our study indicates that injection of new resources through focused active TB case finding and contact tracing efforts can substantially raise the baseline TB case notification among children.…”
Section: Discussionmentioning
confidence: 61%
“…Studies from Pakistan, India, Nepal and Nigeria have shown that intensified case finding can result in large increases in childhood TB case notification [9,[13][14][15]. Our study indicates that injection of new resources through focused active TB case finding and contact tracing efforts can substantially raise the baseline TB case notification among children.…”
Section: Discussionmentioning
confidence: 61%
“…Consequently, a shift from passive to active case DOI: 10.4236/aid.2018.84016 finding approach is crucial to improve TB case detection in Nigeria [24]. [25] maintained that adopting and implementing active case search as part of national policy is essential for finding missing cases of TB.…”
Section: Current Strategies To End Tbmentioning
confidence: 99%
“…The World Health Organization (WHO) and Stop TB Partnership have called for a paradigm shift on how TB services are organised, moving from passive to active case finding -particularly in key populations facing higher risk of TB (2)(3)(4)(5). Furthermore, both agencies specify that TB testing and treatment services must reach at least 90% of these key populations by 2020 (5)(6)(7). Addressing barriers to TB service delivery among key populations is therefore critical to the overall goal of ending the TB epidemic (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, only about 24% of the estimated incident cases of TB in the country were notified [1]. To address this, a number of systematic TB screening strategies have been carried out in Nigeria targeting the general population, TB contacts, persons living with HIV (PLHIV), children, urban and mobile populations (6)(7)(8)(9)(10). In Nigeria's riverine areas, limited land mass leads to uneven distribution of health facilities in the area and residents require costly marine transport -where a return trip may cost up to US$30 to access appropriate health services (11).…”
Section: Introductionmentioning
confidence: 99%